High performance visualization of human tumor growth software - Alias, Norma; Mohd. Said, Norfarizan; Khalid, Siti Nur Hidayah; Sin, Dolly Tien Ching; Phang, Tau Ing (2008)
This paper focused on the implementation of parallel algorithm for the simulation of human tumor growth.The research emphasised on the grand challenge application of breast and brain tumors growth. Based on the present knowledge of the properties of tumors, some mathematical models have been developed by researchers to quantify the proliferation and invasion dynamics of tumors within anatomically accurate heterogeneous human tissue. This paper focuses on the implementation of parallel algorithm for the simulation of hyperbolic equation for breast pressure and parabolic equation of brain tumors growth. The platform for high performance computing of the parallel algorithms run on a distributed parallel computer system. The numerical finite-difference method is focused to design the discreatization of these partial differential equations. The result of finite difference approximation (explicit, Crank-Nicolson and fully implicit methods) will be presented graphically. The implementation of parallel algorithm based on parallel computing system is used to visualize the growth of human tumour. Parallel Virtual Machine (PVM) is emphasized as communication platform in parallel computer systems. The software system functions to enable a collection of heterogeneous computers to be used as synchronize and flexible concurrent computational resource. The parallel performance measurement will be analyzed from the aspect of speedup, efficiency, effectiveness and temporal performance.